2022
DOI: 10.5334/ijic.5500
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Integrated Model of Care for Veterans with Alcohol Problems

Abstract: Introduction: Veterans often do not present with alcohol problems in isolation, they may have a wide range of social, physical, and psychological needs. The aim of this study was to facilitate the development of a co-designed integrated model of care for veterans with alcohol problems.Methods: Following the development model by the Agency for Clinical Innovation, a planning symposium was held in North East of England to engage health and social care planners, public health leads, clinical commissioning groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our study contributes to the evidence base informing the development of effective pathways into Mental Health Services for UK Veterans (Osborne et al, 2021 ). There is also a need to consider how organizations can move toward supporting veteran's transition, through organizational design.…”
Section: Discussionmentioning
confidence: 74%
“…Our study contributes to the evidence base informing the development of effective pathways into Mental Health Services for UK Veterans (Osborne et al, 2021 ). There is also a need to consider how organizations can move toward supporting veteran's transition, through organizational design.…”
Section: Discussionmentioning
confidence: 74%
“…The review identified 47 publications (journal articles n = 23; grey literature reports n = 23; PhD thesis n = 1) from 42 studies. Publications originated from England n = 32, 55–86 United Kingdom n = 10, 87–96 Scotland n = 2, 97,98 Ireland n = 2 99,100 and Wales n = 1 101 . Publications were largely qualitative ( n = 40) or mixed methods ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…Further complexity resulted from rigid commissioning structures. Lack of integration between health and care budgets, not enough focus on prevention, early intervention or whole system approaches meant limited funding was directed towards services co‐produced with communities 69,72,79,84,86,90,94,96 . The emphasis on short‐term goals and funding of pilot projects, which were popular with commissioners, hindered co‐production approaches 64,72,79,93 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations